High incidence and viral load of HHV-6A in a multi-centre kidney transplant cohort - Blazquez-Navarro, Arturo; Roch, Toralf; Wehler, Patrizia; Kaliszczyk, Sviatlana; Bauer, Chris; Thieme, Constantin; Rosiewicz, Kamil S.; Stervbo, Ulrik; Anft, Moritz; Reinke, Petra; Hugo, Christian; Zgoura, Panagiota; et al. (Frontiers in Transplantation, 2023)
Human herpesvirus 6 (HHV-6) is a common opportunistic pathogen in kidney transplant recipients. Two different variants of HHV-6, HHV-6A and HHV-6B, have been identified, of which the latter seems to be dominant. However, it is unclear whether they increase the likelihood of other viral reactivations. We characterized a multi-centre cohort of 93 patients along nine study visits for viral load. We tested for the following viruses: HHV-6A and HHV-6B, the herpesviruses cytomegalovirus (CMV) and Epstein-Barr virus (EBV) and the polyomavirus BK (BKV). We detected HHV-6A viral load in 48 (51.6%) patients, while the incidence of HHV-6B was much lower, being detected in 6 (6.5%) patients. The incidence of HHV-6A was higher than of BKV, CMV and EBV. HHV-6A also demonstrated higher viral loads than the rest of viruses. There was a strong but non-significant association between HHV-6A and HHV-6B as co-infection, whereas no increased incidence of other viruses among patients with HHV-6A reactivation was observed. There was no negative effect of high HHV-6A (>10,000 copies/mL) load on markers of renal graft and hepatic function or blood count twelve months post-transplant. In contrast to previously published data, our results show a clear dominance of HHV-6A in peripheral blood when compared to HHV-6B, with higher incidence and viral load levels. Despite the high HHV-6A loads observed, we did not identify any negative effects on posttransplant outcome.